Frontobasal Aneurysm: Relatively a Rare Neurosurgical Entity - Shrestha, Prabin; Singh, Anish M; Sah, Hemant (Nepal Journal of Neuroscience, 2016)
Distal Anterior Cerebral Artery (DACA) aneurysms are rarer. Its more so with the aneurysm of fronto basal branch of DACA. These aneurysms are smaller in size and are multiple in number in many instances. They rupture easily and present with intracerebral hemorrhage (ICH) in addition to subarachnoid hemorrhage (SAH). Here we present a male patient with SAH and left frontal base interhemispheric ICH. CT angiography showed multiple small aneurysms at right frontobasal artery. Successful clipping of all the aneurysms was done in the single sitting by left pterional craniotomy and subfrontal and interhemispheric approach. Nepal Journal of Neuroscience 12:91-93, 2015